Authorized to heal : gender, class, and the transformation of medicine in Appalachia, 1880-1930 - Barney, Sandra (University of North Carolina Press, 2000)
In this text, the author examines the transformation of medical care in Central Appalachia during the Progressive Era and analyzes the influence of women volunteers in promoting the acceptance of professional medicine in the region.